PENGARUH MODEL COOPERATIVE TIPE THINK PAIR AND SHARE (TPS) TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - kurniati, Mia; Rahmatina, Rahmatina; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study was aimed to find out " The  Effect of Cooperative Learning Models of Think Pair and Share (TPS) Type on Learning Outcomes of Class V Students in Social Studies Lessons in SDN 02 Taeh Baruah District 50 Kota". The research method used is True Experimental Design, in form of Pretest-Posttest Design Group Control. The study population was all fifth grade students of SDN 02 Taeh Baruah, Kabupaten 50 Kota. The sampling technique was Simple Random sampling, and the chosen sample was the VA class as the experimental group and the VB class as the control with total 40 students. Based on data analysis, the average results of posttest the experimental class were 83.35 and the standard deviation was 5.68, while the average posttest in the control class was 77.1 and standard deviation was 7.71. In testing the hypothesis obtained tcount 5.76 and ttable  2.02 at the real level α = 0.05 and df = 38 so tcount > ttable which is 5.76 > 2.02. Then it can be concluded that there is an influence of cooperative model Think Pair Share (TPS) type on the learning outcomes. Keywords: TPS, IPS Learning Outcomes